2009
DOI: 10.1021/jp808957r
|View full text |Cite
|
Sign up to set email alerts
|

Electric Potential Stability and Ionic Permeability of SAMs on Gold Derived from Bidentate and Tridentate Chelating Alkanethiols

Abstract: The interfacial electrochemical properties of self-assembled monolayers (SAMs) on gold derived from a structurally tailored series of monodentate, bidentate, and tridentate chelating alkanethiols were investigated. Specific adsorbates included 1-hexadecanethiol (C16), 2-tetradecylpropane-1,3-dithiol (C16C2), 2-tetradecyl-2-methylpropane-1,3-dithiol (C16C3), 2,2-ditetradecylpropane-1,3-dithiol (C16C16), and 1,1,1-tris(mercaptomethyl)pentadecane (t-C16). Reductive desorption of the SAMs as a function of potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 59 publications
6
53
0
Order By: Relevance
“…Wang et al [28] have recently shown that methyl-terminated loosely-packed SAMs do not display a potential-dependent change in ionic permeability over the same potential range investigated in our study. The high (>10 8 X cm 2 ) and invariant resistance of these monolayers might stem from the lack of amphiphilicity exhibited by the adsorbates or the greater rigidity of their chelating thiol headgroup.…”
Section: Evidence Of Conformational Change Within Ld-mha Samssupporting
confidence: 55%
See 2 more Smart Citations
“…Wang et al [28] have recently shown that methyl-terminated loosely-packed SAMs do not display a potential-dependent change in ionic permeability over the same potential range investigated in our study. The high (>10 8 X cm 2 ) and invariant resistance of these monolayers might stem from the lack of amphiphilicity exhibited by the adsorbates or the greater rigidity of their chelating thiol headgroup.…”
Section: Evidence Of Conformational Change Within Ld-mha Samssupporting
confidence: 55%
“…When the fitted value of R m is very large (>10 7 X cm 2 ), however, Fig. 1 resembles the simple RC circuit (consisting of a film capacitance in series with the solution resistance) that has been employed by others to model fully-packed SAMs in the stability region [28][29][30][31]. Adding complexity to the model through the inclusion of other circuit elements (e.g.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the Bode phase plot (Figure 9) demonstrates that the L-NB SAM behaves as a close-to-ideal capacitive SAM with a phase angle of about 878, which indicates an insulating monoA C H T U N G T R E N N U N G layer; Wang et al suggest that phase angles of 80 to 888 confirm the presence of a highly insulating dielectric material on the electrode surface. [54] Conversely, the phase angle at low frequency for the S-NB SAM was about 778, which indicates that it is less insulating than the L-NB SAM. A more quantitative information about the structures of the monolayers was obtained by fitting the impedance data to the circuit presented in Figure 10, inset.…”
mentioning
confidence: 96%
“…Deviation of the phase angle from 908 (at low frequencies) would suggest an electrical current leakage through the dielectric layer of the Helmholtz capacitor. [52][53][54] At higher frequencies, the total impedance is dominated by the solution resistance and the phase angle decreases towards zero. In this study, the Bode phase plot (Figure 9) demonstrates that the L-NB SAM behaves as a close-to-ideal capacitive SAM with a phase angle of about 878, which indicates an insulating monoA C H T U N G T R E N N U N G layer; Wang et al suggest that phase angles of 80 to 888 confirm the presence of a highly insulating dielectric material on the electrode surface.…”
mentioning
confidence: 99%